Sobre la palinología de algunas especies endémicas e interesantes de Andalucia Oriental. IV - Trigo, Mª del Mar; Hidalgo, Mª Isabel; Bootello, Mª Lourdes; Cabezudo, Baltasar (Acta Botanica Malacitana, 1991)
.